SEOS: Hardware implementation of real-time operating system for adaptability - Ong, S.E. (2013)
Real-Time Operating System (RTOS) is widely used in real time embedded system for computing resource management. It is commonly implemented as fundamental layer in software framework. However, RTOS inevitably causes extra overhead and latency to the system. One of the innovative approaches to improve the overhead and latency is to bring the RTOS out from software framework and implement as hardware component. For past decades, researches had proved that significant performance improvement can be achieved by implementing RTOS in hardware. However, these research outcomes failed to get wide acceptance in commercial products. We postulate that the lacking of interest in commercial community on hardware approached RTOS is due its high level of difficulty in adaptation process. Adapting hardware based RTOS in embedded system requires in depth knowledge on operating system as well as significant amount of manpower resources. This makes the hardware RTOS unpopular despite of the performance offered. This paper proposed a Simple and Effective hardware based Real-Time Operating System (SEOS) designed to provide high adaptability for ease of hardware RTOS adaptation, at the same time significantly improved the performance. Experimental result shows that SEOS has great performance advantages over software based RTOS. Â© 2013 IEEE.